Screening and diagnosis of fetal growth restriction: an expert review - Cecilia Villalaín; Ignacio Herraiz; Ranjit Akolekar; Tamara Stampalija; Francesc Figueras; Fatima Crispi; Tullio Ghi; Giuseppe Rizzo; Ilenia Mappa; Manel Mendoza; Teresa del Moral; Alberto Galindo (The Journal of Maternal-Fetal & Neonatal Medicine)
Background Fetal growth restriction (FGR) is associated to increased perinatal morbidity and mortality. Prenatal identification and subsequent intervention can improve outcomes. Our aim is to provide recommendations regarding the diagnosis and screening of FGR addresing diverse clinical settings—including both high-income and low-to-middle-income countries, as well as both referral and referring centers.Methods An organizational committee assigned a panel of experts different topics regarding screening and diagnosis of FGR. Evidence was prioritized according to the GRADE classification system, with the highest levels of evidence given the greatest weight and organized in practical approach. Although most diagnostic and screening options are described, our aim is not to recommend all but to highlight the evidence for each one and give our recommendations for their use understanding that not all settings will have every option available.Results We provide a practical approach over prescriptive mandates in the definition and screening strategies of FGR in order to avoid unnecessary or excessive interventions and improve perinatal outcomes. While not intended to establish a legal standard of care, we provide a globally relevant resource to support clinicians.Conclusion This document broadens existing frameworks by incorporating updated diagnostic criteria, and context-sensitive recommendations for the screening of this pathology.